Relevansi Pemberian Hukuman Perspektif Al-Ghazali dalam Meningkatkan Motivasi Belajar Peserta Didik Sekolah Menengah Atas - Nagiya; Alfian, Muhammad; Asbupel, Fatnan (CENDEKIA, 2024)
The research aims to see to what extent giving punishment from Imam Al-Ghazali's perspective can influence student learning outcomes, and the relevance of giving punishment in the modern era. The research method used is qualitative with a descriptive approach based on observation, interviews, and documentation. The results of the research show that the application of Al-Ghazali's theory regarding punishment has been used indirectly, although this theory is not yet fully understood by educators at SMA N 3 Sungai Full. The punishment given is following the principles taught by Al-Ghazali. The punishment applied has been proven to be able to increase the learning motivation of most students, although there are challenges such as the helplessness of punishment in some cases. This research concludes that punishment in education needs to be applied wisely and that the principles of Islamic education must be followed to affect student development positively.